A study on safety and feasibility of caesarean myomectomy: at a private institute - Rai, Amrita; Mishra, Manju G. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Myomectomy at the time of caesarean delivery is controversial because of the risk of intractable hemorrhage and increased postoperative morbidity. The incidence of myoma associated with pregnancy is reported at 0.3-5%, with a majority of myomas not requiring surgical intervention during pregnancy or delivery. Recent studies consider it to be safe in selected patients and thus allow women to have a better obstetric outcome in future pregnancies, and to avoid hysterectomy. It relieves symptoms associated with fibroids and negates the need for later surgery or sonographic follow-ups for the fibroid after delivery. Methods: We performed a prospective cohort study of 15 patients with myomas who underwent myomectomy at the time of Caesarean section at MGM Hospital between January 2016 and December 2016. In a predesigned proforma, patient’s details such as age, parity, antenatal course, gestational age at delivery, type of Caesarean section, size and location of the fibroids, blood loss, postoperative morbidity and perinatal outcome were noted. Results: The incidence of hemorrhage in the study group was 20%. There was no significant increase in the incidence of postpartum fever (6.6%), operating time (50 min), and length of postpartum stay (5.6 days). No patient required hysterectomy. Size of fibroid did not appear to affect the incidence of hemorrhage, although intramural myomas were more associated with hemorrhage. Conclusions: This study shows that myomectomy during caesarean section is a safe procedure and is not associated with major intraoperative and postoperative complications.